Innovative Instruction of Islamic Religious Education Teachers in Fostering Independent Character Among Generation Z at Madrasah Aliyah Alkhairaat Pusat Palu - Rizki Rivaldi; Askar; Rustina (Journal of Education and Teaching Learning, 2026)
The background of this research is based on the important role of teachers in creating learning that focuses not only on cognitive aspects but also on the development of independent character among Generation Z students at Madrasah Aliyah Alkhairaat Pusat Palu. The research aims to determine the forms and processes of innovative learning implemented by Islamic Religious Education teachers to shaping the independent character of Generation Z. This research employed a qualitative method with a descriptive approach. Data collection techniques included interviews, observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion. The research findings indicate that innovative learning was implemented through various instructional methods, including Project-Based Learning (PjBL), Problem-Based Learning, group discussions, role-playing groups, students presentations, and the use of digital media. In addition, the learning process was student-centered, with the teacher acting as a facilitator. The innovative learning proved effective in shaping the independent character of Generation Z students, as demonstrated by their attitudes of responsibility, discipline, self-confidence, and the ability to manage the learning process independently. Nevertheless, the implementation still faced several technical and administrative challenges. The research concludes that innovative learning by Islamic Religious Education teachers plays a crucial role in shaping the independent character of Generation Z students through active, participatory, and student-centered learning process.